Related party transactions and firm performance : evidence of tunnelling and propping in China - Guo, Fei (Curtin University, 2008)
Concentrated corporate ownership prevails in most countries, so the relationship between controlling shareholders and minority shareholders is an important principle-agent problem. Tunnelling, the transfer of assets and profit for the benefit of controlling owners, is the most important way of expropriating small shareholders. While tunnelling is rampant in emerging economies and even some developed countries, related research lacks convincing evidence. On the other hand, large shareholders sometimes use private funds to prop up firms in financial distress. Although there is plenty of anecdotal and indirect evidence on propping, it lacks direct large-sample examination. This study presents a pooled cross-sectional analysis of 4373 publicly listed companies in China between 2001 and 2004. The analysis not only examines the effects of various variables on the exploitation of related party transactions by controlling owners for tunnelling and propping, and also investigates the effects of tunnelling and propping on firm performance and valuation. The study reveals that the presence of controlling shareholders and higher control rights lead to higher levels of tunnelling. Conversely the existence of other large shareholders reduces the magnitude of tunnelling. In addition, the study shows that pyramidal-controlled firms and firms owned by the State display more incidences of tunnelling. When firms have better investment opportunity, however, their controlling shareholders tend to divert fewer funds for their private gains. It is also found that controlling shareholders offer funds to financially stricken firms under their control. This is the first study that finds direct evidence on the occurrence of propping although not all badly-performing firms are propped up.While tunnelling negatively affects operating performance and firm valuation, propping has a positive effect on firm valuation. The occurrence and magnitude of tunnelling is greater than that of propping. Propping only occurs to partial firms in financial distress, yet there is no improvement in those firms’ performance. As propping from new controlling owners is more a way of back-door listing, they tend to engage in tunnelling when their control is secure. In short, when legal protection of minority shareholders is weak, controlling owners tend to tunnel for private benefit. Hence policymakers and regulators must recognise that to eliminate widespread expropriation, the establishment of strong corporate governance in well-functioning institutions and strong legal enforcement is important. Lower levels of tunnelling in years 2003 and 2004 justify the positive effect of stringent regulation. Yet, more needs to be undertaken beyond the legal and regulatory level such as an allowance for diversified corporate ownership and the transformation of non-floatable shares to be floated on the exchange to align interests of large and minority shareholders.